2021
DOI: 10.1002/pc.25991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of poly(vinylidene fluoride)/carbon black composites, manufactured by selective laser sintering

Abstract: In this study, we investigated the viability of processing composites based on poly(vinylidene fluoride) and carbon black (PVDF/CB) applying the selective laser sintering (SLS) process, with equipment constructed in the laboratory. In the first step, the powder particles of PVDF and CB were characterized by scanning electron microscope, particle size distribution, differential scanning calorimetry, and thermogravimetric analysis. In order to evaluate the effect of CB on the morphology, electrical conductivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The mechanical and thermal properties of PA6/clay nanocomposite fabricated with SLS process were studied by Kim and Creasy, [21] who reported that clay nanoparticles increased the viscosity and mechanical properties of the nanocomposite. Analysis of the mechanical properties of nanocomposites produced by 3D printing has been also studied by Guaricela et al [22] and Aktitiz et al [23,24] A review of previous works on the polymer nanocomposites indicated that enhancement of the mechanical properties of nanocomposites fabricated by the SLS process has been recently came into consideration. However, the SLS process has not been used to produce PA6/CNT nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical and thermal properties of PA6/clay nanocomposite fabricated with SLS process were studied by Kim and Creasy, [21] who reported that clay nanoparticles increased the viscosity and mechanical properties of the nanocomposite. Analysis of the mechanical properties of nanocomposites produced by 3D printing has been also studied by Guaricela et al [22] and Aktitiz et al [23,24] A review of previous works on the polymer nanocomposites indicated that enhancement of the mechanical properties of nanocomposites fabricated by the SLS process has been recently came into consideration. However, the SLS process has not been used to produce PA6/CNT nanocomposite.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical and thermal properties of PA6/clay nanocomposite fabricated with SLS process were studied by Kim and Creasy, [ 21 ] who reported that clay nanoparticles increased the viscosity and mechanical properties of the nanocomposite. Analysis of the mechanical properties of nanocomposites produced by 3D printing has been also studied by Guaricela et al [ 22 ] and Aktitiz et al [ 23,24 ]…”
Section: Introductionmentioning
confidence: 99%
“…This is because the high shear mixing of traditional processing would destroy the segregated networks. Moreover, compared with other reported SLS-printed conductive composites in literature studies, , , the conductivity of SLS-printed SWCNTs@PDMS-CANs composites could reach ∼10 –1 S m –1 at a much lower content of ∼0.1 wt %, as listed in Figure (i). This is attributed to the following four reasons: (1) the large aspect ratio and higher electrical properties of SWCNTs; (2) the efficient dispersion of SWCNTs through the liquid-phase deposition and adsorption process under ultrasound; (3) the preservation of 3D segregated networks by SLS quasi-static printing using the SWNCTs-wrapped PDMS-CANs powders; and (4) compared to crystalline nylon, the relatively high viscosity of amorphous PDMS-CANs prevents the SWCNT networks from breaking during melt fusion.…”
Section: Resultsmentioning
confidence: 57%
“…[264] With these characteristics, the most widely utilized smart piezoelectric material is poly(vinylidene fluoride) (PVDF), having a simple chemical formula of CH 2 CF 2 and has other attractive properties like good tensile and shear stability, good chemical hindrance, and significant piezoelectricity. [270,271] The piezoelectricity and bio-responsivity of PVDF with graphene oxide (GO) showed an excellent electrically charged scaffold for bone and tissue engineering. [272] Similarly, another functional copolymer of PVDF is trifluoroethylene (PVDF-TFE) nanoparticles, which exist in the β-phase, having high piezoelectric constant and electromechanical activity.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%